Comparison of P25 and nanobelts on Kruppel‐like factor‐mediated nitric oxide pathways in human umbilical vein endothelial cells. Issue 4 (10th October 2021) - Gu, Manyu; Wang, Shuyi; Cao, Wandi; Yan, Dejian; Cao, Yi
Abstract: Recently, we reported that titanium dioxide (TiO2 ) materials activated endothelial cells via Kruppel‐like factor (KLF)‐mediated nitric oxide (NO) dysfunction, but the roles of physical properties of materials are not clear. In this study, we prepared nanobelts from P25 particles and compared their adverse effects to human umbilical vein endothelial cells (HUVECs). TiO2 nanobelts had belt‐like morphology but comparable surface areas as P25 particles. When applied to HUVECs, P25 particles or nanobelts did not induce cytotoxicity, although nanobelts were much more effective to increase intracellular Ti element concentrations compared the same amounts of P25 particles. Only nanobelts significantly induced THP‐1 adhesion onto HUVECs. Consistently, nanobelts were more significant to induce the expression of intracellular adhesion molecule‐1 (ICAM1) and the release of soluble ICAM‐1 (sICAM‐1), indicating that nanobelts were more potent to induce endothelial activation in vitro. As the mechanisms for endothelial activation, both P25 and nanobelts reduced the generation of intracellular NO as well as the expression of NO regulators KLF2 and KLF4. Combined, the results from this study indicated that the different morphologies of P25 particles and nanobelts only changed their internalization into HUVECs but showed minimal impact on KLF‐mediated NO signaling pathways. Abstract : Nanobelts of similar surface areas were synthesized from P25 particles. When applied to human umbilical vein endothelial cells (HUVECs), nanobelts were more effective to induce endothelial activation compared with P25. However, both types of materials reduced intracellular NO and decreased the expression of NO regulators KLF2 and KLF4 to similar extent. Since P25 particles and nanobelts may only differ in morphologies, there results suggested that morphologies had minimal impact on KLF‐mediated NO signaling pathways in Ti‐based material‐exposed HUVECs.